2001
DOI: 10.1037/0096-3445.130.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive arithmetic across cultures.

Abstract: Canadian university students either of Chinese origin (CC) or non-Asian origin (NAC) and Chinese university students educated in Asia (AC) solved simple-arithmetic problems in the 4 basic operations (e.g., 3 + 4, 7 -3, 3 X 4, 12 •*• 3) and reported their solution strategies. They also completed a standardized test of more complex multistep arithmetic. For complex arithmetic, ACs outperformed both CCs and NACs. For simple arithmetic, however, ACs and CCs were equal and both performed better than NACs. The super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
608
13
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(681 citation statements)
references
References 63 publications
58
608
13
2
Order By: Relevance
“…This difference between subtraction and addition has also been found in adults. LeFevre, De Stefano, Penner-Wilger, and Daley's (2006) participants reported retrieval on 82% of easy problems (minuend < 10) but on only 42% of hard problems, results echoing those reported by Campbell and Xue (2001), who observed retrieval on 73 and 42% of easy and hard problems, respectively. For sake of comparison, LeFevre, Sadesky, and Bisanz (1996) reported a retrieval rate of 71% in adults solving the 100 additions with operands from 0 to 9.…”
Section: Mental Subtraction and Additionsupporting
confidence: 65%
“…This difference between subtraction and addition has also been found in adults. LeFevre, De Stefano, Penner-Wilger, and Daley's (2006) participants reported retrieval on 82% of easy problems (minuend < 10) but on only 42% of hard problems, results echoing those reported by Campbell and Xue (2001), who observed retrieval on 73 and 42% of easy and hard problems, respectively. For sake of comparison, LeFevre, Sadesky, and Bisanz (1996) reported a retrieval rate of 71% in adults solving the 100 additions with operands from 0 to 9.…”
Section: Mental Subtraction and Additionsupporting
confidence: 65%
“…According to Campbell and Xue (2001), there are three strategy-related sources of the problem-size eVect in adults: less frequent retrieval use for large than for small problems, lower retrieval eYciency for large than for small problems, and lower procedural eYciency for large than for small problems. In the current study, we investigated which of these sources determine the problem-size eVect in children.…”
Section: Evects Of Problem Size On Arithmetic Strategy Usementioning
confidence: 99%
“…Adult studies consistently show operation-related diVerences in both strategy selection and strategy eYciency (e.g., Campbell, 1995;Campbell & Xue, 2001;Hecht, 1999;Imbo, Vandierendonck, & Rosseel, 2007, in press). Generally, retrieval is used more frequently in multiplication than in addition, whereas both retrieval and procedural eYciencies are higher in addition than in multiplication.…”
Section: Evects Of Operation On Arithmetic Strategy Usementioning
confidence: 99%
“…For example, Dehaene and colleagues (2008) found that their sample of American adults had linear representation of 0-10 symbolic numbers (in English and in Spanish, with the latter being a second language for the participants) and 1-10 dots, but not of 1-100 dots or 1-10 tones, both of which were logarithmically mapped. Third, although we expected similar developmental trends in Chinese children as in Western children, we expected that the shift from logarithmic to linear representation would occur earlier in Chinese children than has been found in American children because of the former's advantage in early mathematics (e.g., Campbell & Xue, 2001;Chen & Stevenson, 1995;Miller et al, 1995;Stevenson et al, 1990Stevenson et al, , 1993. This hypothesis was a downward extension of Siegler and Mu's (2008) findings from kindergarteners to preschoolers.…”
Section: Introductionmentioning
confidence: 85%
“…This lack of research on young children is especially relevant to Chinese children who begin preschool at 3 years of age and receive formal education about numbers. Previous studies have documented Chinese children's superior performance in mathematics across all age groups as compared with their Western counterparts (e.g., Campbell & Xue, 2001;Chen & Stevenson, 1995;Miller, Smith, Zhu, & Zhang, 1995;Stevenson, Chen, & Lee, 1993;Stevenson et al, 1990). Would Chinese 3-and 4-year-olds then have developed linear representations of numbers after a year or so of learning numbers in preschool?…”
Section: Introductionmentioning
confidence: 99%